2011
DOI: 10.3109/14767058.2011.607563
|View full text |Cite
|
Sign up to set email alerts
|

The sleep protection in the preterm infants

Abstract: The importance of sleep in the development is only now beginning to be understood: sleep and established sleep cycles have an important role in the normal neurosensory and cortex development. The biological basis of sleep organization has been highlighted by several studies however environmental differences can affect the sleep patterns in preterm infants in the NICU. Sleep disorders are related to several physiological conditions but it is important to know the relationship between sleep organization and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Although nap time proposed by the NICU have been effective in promoting sleep of those premature infants investigated, the results allow concluding that in the remaining 20 hours there was no environmental management, total sleep time was only 11.6 hours. Proportionally, this finding shows that the total sleep time of newborns was lower than recommended by the literature, which highlights they require 17-22 hours of sleep, depending on gestational age (18)(19) . The data from observations allowed us to infer that the total sleep time was lower in the absence of environment management due to handling of newborns by unit staff and cry arising from care, which may have boosted the increase in the noise level and the consequent environmental acoustics change in general.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although nap time proposed by the NICU have been effective in promoting sleep of those premature infants investigated, the results allow concluding that in the remaining 20 hours there was no environmental management, total sleep time was only 11.6 hours. Proportionally, this finding shows that the total sleep time of newborns was lower than recommended by the literature, which highlights they require 17-22 hours of sleep, depending on gestational age (18)(19) . The data from observations allowed us to infer that the total sleep time was lower in the absence of environment management due to handling of newborns by unit staff and cry arising from care, which may have boosted the increase in the noise level and the consequent environmental acoustics change in general.…”
Section: Discussionmentioning
confidence: 50%
“…The data from observations allowed us to infer that the total sleep time was lower in the absence of environment management due to handling of newborns by unit staff and cry arising from care, which may have boosted the increase in the noise level and the consequent environmental acoustics change in general. This result also indicates that premature infants are being deprived of sleep, which can cause various deleterious effects such as stress, irritability, increased heart rate, basal metabolism with consequent weight loss, increased susceptibility to infections and changes in pain perception (14,18,20) . Sleep deprivation may be related to the impairment of sick children, generating an increase in hospitalization costs and delaying hospital discharge (20) .…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4) In modern neonatal intensive care units (NICU), preterm infants are generally subjected to multiple sensory and physical stimuli associated with excessive handling by health teams.…”
Section: Introductionmentioning
confidence: 99%
“…(12) Studies have found that excessive handling and sleep deprivation in preterm infants may impair neuromotor development, induce hyperexcitability, trigger or exacerbate psychiatric diseases, and cause excessive daytime sleepiness. (1,(13)(14)(15) Furthermore, sleep is the main behavioral state of preterm infants and constitutes an important basic need. It is conducive to maturation of the central nervous system, memory consolidation, learning, energy maintenance, thermoregulation, promotion of protein synthesis, and the production of certain hormones, such as growth, thyroid stimulation, melatonin, prolactin, renin, and cortisol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation